Penurunan Kadar Gula Darah pada Monyet Ekor Panjang Obes dengan Pemberian Nikotin Dosis Rendah (DECRESE IN BLOOD SUGAR LEVEL IN LONG TAILED OBESE MACAQUES GIVING WITH LOW DOSE NICOTINE) - Choliq, Chusnul; Sajuthi, Dondin; Suparto, Irma Herawati; Astuti, Dewi Apri; Wulansari, Retno (Jurnal Veteriner; Vol 14 No 2 (2013), 2013)
The aim of the study was to evaluate the role of low dose nicotine on the profile of blood glucose and  â-cell of pancreatic islets.  Fourteen adult (aged 6 – 8 years) male cynomolgus monkeys grouped based ontheir Body Mass Index (BMI) into preobese (BMI=23.65 – 25.00) and obese (BMI e” 26.00) were used inthis study. Subsequently animals were grouped into four:  (i) preobese monkeys with nicotine (pOb+), (ii)obese monkeys with nicotine (Ob+), (iii) preobese monkeys without nicotine (pOb-), and (iv) obese monkeyswithout nicotine (Ob-). Animals in the nicotine groups were fed with high fat diet mixed with nicotine dose0.5–0.75mg/kg body weight/day for three months and the others were fed Monkey Chow® only as thecontrol group. Blood samples were collected every month for glucose analysis and necropsy was performedat the end of study. Pancreas tissues were processed histologically and stained using  immunohistochemicalmethod. The results showed that the blood glucose either preobese (28.37%) or  obese (33.72%) animals inthe nicotine groups significantly decrease (p<0.05) during the study period in comparison to the controlgroup.  Based on brown color intensity of granules cytoplasm of insulin producing cells or immunoreactiveâ-cells, it is shown that the cells of animals in the non nicotine group were more reactive than those in thenicotine groups. In conclusion, there was positive effect of low dose nicotine in maintaining the bloodglucose level in normal range by stimulation of islet cells proliferation to maintain the production ofinsulin in the pancreatic islet.
Keywords: animal model, ?-cells, cynomolgus monkey, nicotine, obesity